Agomelatine: A review for general practitioners - K. Outhoff (South African Family Practice)
Agomelatine is a novel melatonergic antidepressant that restores disrupted biological rhythms, essentially by resetting the circadian clock. Two different, non-monoaminergic, and possibly synergistic pathways, appear to be involved in its mechanism of action. Agomelatine is a melatonin 1 (MT1) and melatonin 2 (MT2) receptor agonist and serotonin (5-hydroxytryptamine) 2C (5-HT2C) receptor antagonist. It is effective in treating moderate-to-severe depression, alleviating the symptoms of anxiety, and restoring the disrupted sleep patterns that often result from this potentially devastating disease. Agomelatine is generally well tolerated with little, if any, propensity for antidepressant-induced sexual dysfunction, weight gain, or discontinuation reactions. However, it has the potential to cause temporary hepatotoxicity, and liver functions need to be monitored as a result. Clinically, meaningful drug interactions are unlikely, with the exception of co-administered potent cytochrome P 1A2 (CYP1A2) enzyme inhibitors, which may increase agomelatine’s plasma levels significantly. Agomelatine represents an interesting addition to the antidepressant market.